Philippine labor, 1968-1977 a select and annotated bibliography - Salazar, Elizabeth L. (Institute of Library Science, University of the Philippines Diliman, 1979)
Industrial relations is fast developing as a discipline and as an area study in the Philippines. A survey of the literature reveals that the quantity, form and substance as well as writers in this dynamic field are increasing specially during the last ten years.